2019
DOI: 10.3389/fneur.2019.00778
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on the Involvement of the Kynurenine Pathway in Stroke: Pre-clinical and Clinical Evidence

Abstract: Background: Stroke is the second leading cause of death after ischemic heart disease and the third leading cause of disability-adjusted life-years lost worldwide. There is a great need for developing more effective strategies to treat stroke and its resulting impairments. Among several neuroprotective strategies tested so far, the kynurenine pathway (KP) seems to be promising, but the evidence is still sparse. Methods: Here, we performed a systematic review of preclinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 76 publications
3
50
0
Order By: Relevance
“…TRP levels in neurovascular patients were significantly lower as compared with controls, with significantly lower levels of TRP in AIS patients compared to patients with SCAS. The result is in accordance with systematic Colpo's review evaluating the involvement of KP in stroke [24] and with Wang's review about dysregulation of KP in inflammation [27]. Accordigly, neurovascular patients had both enhanced inflammation marker NEO (AIS patients significantly) and KTR ((SCAS patients significantly) as compared with controls.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…TRP levels in neurovascular patients were significantly lower as compared with controls, with significantly lower levels of TRP in AIS patients compared to patients with SCAS. The result is in accordance with systematic Colpo's review evaluating the involvement of KP in stroke [24] and with Wang's review about dysregulation of KP in inflammation [27]. Accordigly, neurovascular patients had both enhanced inflammation marker NEO (AIS patients significantly) and KTR ((SCAS patients significantly) as compared with controls.…”
Section: Discussionsupporting
confidence: 88%
“…However, KYN concentrations in neurovascular patients were not significantly different compared to controls, nevertheless KYN concentrations in SCAS patients were significantly higher compared to AIS patients. The results do not correspond neither to Colpo's review for stroke [24] nor to Pawlak's results about KYN and QA linked to carotid atherosclerosis in patients with end-stage renal disease [43]. However, Ormstad et al also did not found significant differences of both KYN levels and KTR values in patients with AIS [44].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, these striking similarities were observed within the first hour in humans and first half hour in rats after resuscitation, indicating that unlike previous studies, alterations in the tryptophan and kynurenine pathway metabolites occur almost immediately postresuscitation. A higher kynurenine to tryptophan ratio observed in both preclinical and clinical studies of brain injury [48][49][50][51] and cardiovascular disease 52 indicated worse clinical outcomes implicating oxidative and inflammatory stress. Controversially, ischemic damage induced by CA may increase kynurenic acid, which may serve a protective role, as kynurenic acid has neuroprotective effects, while 3-hydroxyanthranilic acid and downstream quinolinic acid have a proclivity for neurotoxicity 50,53 .…”
Section: Discussionmentioning
confidence: 99%
“…7 Some preclinical studies suggest the involvement of KP in the pathophysiology of stroke and its potential as a pharmacological target for stroke and related complications. 8 It has been demonstrated that kynurenine is an endogenous ligand for the aryl hydrocarbon (AH) receptor. 9 More recently, it was established that some compounds formed during the KP might have either neuroprotective or neurotoxic properties, 1c and they have the potential to be used as specific biomarkers for patients diagnosed with amyotrophic lateral sclerosis.…”
Section: Scheme 1 Metabolism Of L-tryptophan Via the Kynurenine Pathwmentioning
confidence: 99%